ANALISIS PENGARUH PELAYANAN KARYAWAN YANG BERORIENTASI PELANGGAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP RETENSI PELANGGAN: (STUDI EMPIRIS PADA SALON KECANTIKAN DI KOTA AMBON) - Poserattu V. Alfonso (Jurnal Administrasi Terapan, 2023)
This study aims to examine the effect of customer-oriented employee service on customer satisfaction and retention. This study also examines the mediating effect of customer satisfaction on the effect of customer-oriented employee service on customer retention. Respondents selected in this study were respondents who use beauty salon services and live in Ambon City. Sampling was done through purposive sampling criteria. The number of respondents that can be used is 193 people from 210 questionnaires distributed. To find out the level of validity and reliability of the data, validity and reliability tests were carried out. Hypothesis testing is done using multiple linear regression analysis. The results showed that there were 3 (three) hypotheses which showed significant results in this study. This study found that customer-oriented employee service has a very strong and positive effect on customer satisfaction. This study also found that customer satisfaction has a very strong and positive effect on customer retention. Furthermore, this study found that customer-oriented employee service is significant on customer retention. The results of this study also describe customer satisfaction as mediating the relationship between customer-oriented employee service and customer retention. Keywords: Custmer Oriented Employee Service, Satisfaction, Retention.